Impact of fibronectin type III domain-containing family in the changes in metabolic and hormonal profiles during peripartum period in dairy cows - Daudon, Mathilde; Ramé, Christelle; Estienne, Anthony; Price, Christopher; Dupont, Joëlle (Frontiers in Veterinary Science, 2022)
The peripartum period is an important period in dairy cow frequently associated to excessive lipolysis due to Negative Energy Balance (NEB). Some indicators like β-hydroxybutyrate (BHBA) and Non-Esterified Fatty Acids (NEFA) are biomarkers of NEB in dairy cows. Moreover, the involvement of adipokines like adiponectin and leptin during peripartum period is well described. Nevertheless, little is known about the myokines during peripartum period. Fibronectin type III domain-containing proteins (FNDC) are myokines and adipokines recently involved in the metabolic dysfunctions. This study aimed to evaluate some FNDCs (FNDC5, 4, 3A and B) as potential plasma and adipose tissue indicators of NEB in cattle. We investigated plasma FNDCs concentrations and adipose tissue FNDCs gene expression during the peripartum period (four weeks before the estimated calving day (4WAP), one (1WPP) and 16 (16WPP) weeks postpartum in two groups of dairy cows selected with low (LNEB, n=8) and high NEB (HNEB, n=13) at 1WPP. Using specific bovine ELISA assay, only plasma FNDC5 concentration varied during the peripartum period in both LNEB and HNEB animals. It was increased at 1WPP as compared to 4WAP and 16 WPP. FNDC5 plasma concentrations was negatively correlated with Dry Matter Intake (DMI), Live Body Weight (LBW), Variation of Empty Body Weight (VEBW) and glucose concentrations and positively correlated with plasma non-esterified fatty acids and β-Hydroxybutyrate (BHBA) concentrations. By RT-qPCR, we showed that FNDC5 gene is highly expressed in subcutaneous tissue and we confirmed this result at the protein level by immunoblot. We also observed that FNDC5 gene expression in subcutaneous adipose tissue was increased at 1 WPP as compared to 4WAP and 16WPP in HNEB group and increased at 1 WPP as compared to 4 WAP in LNEB group. In addition, it was higher in HNEB than in LNEB animals during early lactation. Finally, we showed that recombinant human irisin (a fragmented product of FNDC5) increased the release of glycerol and mRNA levels for ATGL (adipose triglyceride lipase) and HSL (Hormone-sensitive-lipase) similarly in bovine and human adipose tissue explants. Taken together, FNDC5 expressed in bovine adipose tissue could be involved in the lipid mobilization and NEB regulation in cattle.